(3GdJShjGJ GdLQOjI hGdEaUGM GdeMGSHjs - (3YHO GdfGUQ eMeO SjO(B, (3OQhjTs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2010)
(3GdeYGLI GdeMGSHjI dLQO GdfbOjI(B- (3GdeYGdLI GdeMGSHjI dLQO GdeOjfhf(B- (3GdeYGdLI GdeMGSHjI dLQO ChQGb GdbHV hGddhGRe(B- (3GdeYGdLI GdeMGSHjI dLQO GdGSJKeGQGJ aj GdChQGb GdeGdjI bUjQI GdGLd(B- (3GdeYGdLI GdeMGSHjI dLQO eNRhf GdHVGYI(B- (3GdeYGdLI GdeMGSHjI dLQO GdGUhd GdKGHJI(B- (3GdeYGdLI GdeMGSHjI dLQO GdGUhd ZjQ GdedehSI hGdehGQO GdWHjYjI(B- (3GdeYGdLI GdeMGSHjI dLQO GdGdJRGeGJ hMbhb GdedcjI(B- (3GdbhGFe GdeGdjI(B.s
(3edGMb U(B.373 (3HjHdjhZQGajG(B:(3U(B.455s
Keywords: (3GdeGdjI GdYGeI(B- (3eMGSHIs; (3GdeMGSHI GdJMdjdjIs